Pengawasan Dinas Lingkungan Hidup Provinsi Jawa Timur Terhadap Limbah Cair Industri Baja dan Pengolahannya - Titania Farah Nabila; Muhammad Mirwan (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
An internship is an independent student activity carried out on campus to gain practical work experience in accordance with their field of specialization through observation and participation methods. The method used in this study is a quantitative-descriptive method. This method combines empirical research in which the data is in the form of numbers and research that seeks to describe a symptom, event, event that is happening at the present time. The wastewater treatment for the steel industry uses the Sewage Treatment Plant process, which is a domestic wastewater treatment system that aims to reduce the content of parameters that have the potential to pollute the environment. These parameters include BOD, COD, Ammonia, TSS, Total Coliform, pH, and others. The decrease in parameter levels occurs due to physical, chemical and biological processes that occur at the Compliance Point Well (STP). Domestic waste testing is carried out with a frequency of once a month, with monitoring well monitoring test results showing no contamination of groundwater by heavy metal content (key parameter) as a result of the production process as indicated in the monitoring discussion. The results of this study aim that the industry can be responsible for treating the waste water produced in accordance with existing regulations.